2017
DOI: 10.1152/ajprenal.00074.2017
|View full text |Cite
|
Sign up to set email alerts
|

Urine RAS components in mice and people with type 1 diabetes and chronic kidney disease

Abstract: The pathways implicated in diabetic kidney disease (DKD) are largely derived from animal models. To examine if alterations in renin-angiotensin system (RAS) in humans are concordant with those in rodent models, we measured concentration of angiotensinogen (AOG), cathepsin D (CTSD), angiotensin-converting enzyme (ACE), and ACE2 and enzymatic activities of ACE, ACE2, and aminopeptidase-A in FVB mice 13-20 wk after treatment with streptozotocin ( = 9) or vehicle ( = 15) and people with long-standing type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 70 publications
1
34
1
Order By: Relevance
“…Several studies using diabetic models show activation of the RAS locally within the kidney by glucose, including an increase in Ang II production [33][34][35][36]. Additional evidence comes from findings of increased RAS components in the kidney and urines from rodent models of diabetic kidney disease (DKD) and in patients with DKD [16,37] and non-diabetic CKD [38,39]. There is a need for new approaches to counteract RAS overactivity that expand and improve on the existing ones which are based on blockade of Ang II formation or action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using diabetic models show activation of the RAS locally within the kidney by glucose, including an increase in Ang II production [33][34][35][36]. Additional evidence comes from findings of increased RAS components in the kidney and urines from rodent models of diabetic kidney disease (DKD) and in patients with DKD [16,37] and non-diabetic CKD [38,39]. There is a need for new approaches to counteract RAS overactivity that expand and improve on the existing ones which are based on blockade of Ang II formation or action.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a diabetic model with local kidney but not systemic RAS over-activity [13], long-term augmentation of circulating ACE2 activity was not sufficient to alter glomerular pathology, GFR or albuminuria [13]. These observations provide the rationale for the development of shorter forms of ACE2 with a molecular size that render them filtrable by the kidney and, therefore, potentially useful therapeutically to amplify ACE2 activity in forms of kidney disease with an overactive local RAS in the kidney [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is a gap, and limited research focus was on the risk predictors for kidney disease. Some of the proposed candidates are neutrophil gelatinase-associated lipocalin, angiotensinogen, renin, and NEP (20,29,33,42,49,56). In addition, other RAS enzymes, such as urinary ACE and ACE2, have also been investigated as potential new markers for hypertension (6) and diabetes (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SHR had high serum levels of renin in vivo, which usually cause renal damage and other symptoms, such as hyperdipsia, polyuria, proteinuria, and so on [35]. The volume of drinking water (Fig.…”
Section: Resultsmentioning
confidence: 99%